Examination of Autoantibody Status and Clinical Features Associated With Cancer Risk and Cancer‐Associated Scleroderma. Issue 4 (April 2015) - Shah, Ami A.; Hummers, Laura K.; Casciola‐Rosen, Livia; Visvanathan, Kala; Rosen, Antony; Wigley, Fredrick M.
Abstract : Objective: We previously reported a contemporaneous onset of cancer and scleroderma in patients with anti–RNA polymerase III antibodies, and we identified a biologic link between cancer and scleroderma. This investigation was designed to further evaluate whether autoantibody status and other characteristics are associated with cancer and a clustering of cancer with scleroderma onset. Methods: Logistic regression analysis was performed to assess the relationship of 2 outcomes, cancer (model 1) and a short (±2 years) cancer–scleroderma interval (model 2), with autoantibody status and scleroderma covariates. Results: Of 1, 044 scleroderma patients, 168 (16.1%) had cancer. In the adjusted model 1, only older age at scleroderma onset (odds ratio 1.04 [95% confidence interval 1.02–1.05]) and white race (odds ratio 2.71 [95% confidence interval 1.22–6.04]) were significantly associated with an increased overall risk of cancer. In the adjusted model 2, only anti–RNA polymerase III positivity (odds ratio 5.08 [95% confidence interval 1.60–16.1]) and older age at scleroderma onset (odds ratio 1.04 [95% confidence interval 1.00–1.08]) were significantly associated with a short cancer–scleroderma interval. While anti–RNA polymerase III positivity was associated with a short cancer–scleroderma interval independent of age at scleroderma onset, the cancer–scleroderma interval shortened with older age at scleroderma onset in other antibody groups (Spearman's correlation P < 0.05), particularly among patients with anti–topoisomerase I antibodies and patients who were negative for anticentromere, anti–topoisomerase I, and anti–RNA polymerase III antibodies. Conclusion: Increased age at scleroderma onset is strongly associated with cancer risk overall. While anti–RNA polymerase III status is an independent marker of coincident cancer and scleroderma at any age, a clustering of cancer with scleroderma is also seen in patients with anti–topoisomerase I and other autoantibody specificities who develop scleroderma at older ages.